Protorhabditis hortulana sp. n. (Rhabditida, Protorhabditidae) from southern Iberian Peninsula, one of the smallest free-living soil nematodes known, with a compendium of the genus - Abolafia, Joaquín; Peña-Santiago, Reyes (Zootaxa, 2016)
A new species of the genus Protorhabditis is described from agricultural areas in the South East of the Iberian Peninsula. Protorhabditis hortulana sp. n. is distinguished by its very small body length (189–222 μm in females), lateral field with two longitudinal wings, lip region rounded with fused lips, stoma 10–13 μm long lacking glottoid apparatus, pharynx with distinctly swollen metacorpus, excretory pore and deirids at basal bulb level, female reproductive system outstretched and spermatheca with self-sperm, vulva slightly postequatorial (V=54–62), female tail conoid (14–19 μm, c= 11.7–17.6, c’= 1.6–2.4) with finely rounded tip, and males unknown. Description, measurements and illustrations, including SEM photographs are provided. A compendium of species of Protorhabditis is also given and illustrated.